Enumeration of Plants from Rander Area and Environs in Gujarat - Solanky, I. N.; Joshi, J. V.; Patel, H. K. (Indian Forester, 1972)
In the present paper 432 taxa of 98 Angiosperm and one Gymnosperm families are enumerated, collected from the present area during 1965-68. 370 are dicotyledons, 1 gymnosperm and 61 monocotyledons.